Association between sports participation history and age of first exposure to high-risk sports with concussion history. Issue 3 (4th May 2023) - Caccese, Jaclyn; Schmidt, Julianne; Moody, Jena; Broglio, Steven; McAllister, Thomas; McCrea, Michael; Pasquina, Paul; Buckley, Thomas; Investigators, CARE Consortium
ABSTRACT: The purpose of this study was to examine the association between sports participation history, including estimated age of first exposure (eAFE) to high-risk sports, and concussion history in first year (i.e., freshmen) collegiate athletes. Athletes increased their odds of sustaining a pre-college concussion by 5% [odds ratio(OR) = 1.05 (95%CI:1.05–1.06)] for each additional year of contact sports participation – 24% of all student athletes reported one or more pre-college concussions. When eAFE was analysed dichotomously at age 12, a greater proportion of those who started playing football before age 12 reported a positive concussion history compared to those who started playing football at age 12 or later (Х 2 = 4.483, p = 0.034, Phi = 0.049). When eAFE was analysed continuously, later eAFE to women's high-risk sports was associated with a lower likelihood of sustaining a pre-college concussion [OR = 0.93 (95%CI:0.88–0.98)]. Our findings suggest that there is a relationship between eAFE to football and to women's high-risk sports and concussion history.